Sistem Informasi Penjualan Berbasis Web Pada RM Sinar Minang - Melinda; Muslim Hidayat; M Alif Muwafiq Baihaqy (Yayasan Pendidikan Penelitian Pengabdian ALGERO, 2021)
Rumah Makan (RM) Padang is a restaurant business that sells or serves a variety of Minangkabau culinary or cuisine originating from West Sumatra. This restaurant is very famous in Indonesia and even the world. One of them is RM Padang Sinar Minang which is in Purbalingga, the restaurant provides a lot of food menus. Some of them are rendang, minced, gravel, snapper, tripe and iso. In monthly reporting activities, at RM Sinar Minang, the handwriting system is still being applied (manual). Admin difficulties in writing handwritten financial reports (manual) and in thepayment system. whose sales records are still handwritten (manual), of course this kind of activity must be updated with the development of technology. The writing of financial statements that occurs is the amount of money that is at the cashier with the amount of money that is on the record of the food sold is not in sync / not the same. So it can be concluded that in writing the record of the food sold, there were problems such as forgetting to write the food that had been sold. Based on these things, the idea emerged to create a Web-Based Sales Information System at RM Sinar Minang. This system is expected to make it easier for admins/owners to collect data and can serve as a neat monthly report for agencies.